2020
DOI: 10.3390/jcm9010176
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperuricemia on the Prognosis of IgA Nephropathy are More Potent in Females

Abstract: Hyperuricemia is a potential risk factor for immunoglobulin A nephropathy (IgAN) progression but its sex-specific effects on IgAN progression remain unclear. This study aimed to determine the effect of serum uric acid on IgAN progression and whether its effect varied according to sex. A total of 4339 patients who diagnosed with IgAN by renal biopsy were retrospectively analyzed. We assessed the association of serum uric acid on IgAN progression using Kaplan–Meier survival analyses and Cox proportional hazards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
13
1
Order By: Relevance
“…The AUC for male patients was 0.5728 ± 0.2029 ( Figure 4C). Our results revealed that the SUA level was a valuable indicator in predicting the prognosis of IgAN patients, especially in female patients, which is consistent with the research of Oh et al (Oh et al 2020).…”
Section: The Value Of the Sua Level In Predicting Renal Prognosissupporting
confidence: 93%
“…The AUC for male patients was 0.5728 ± 0.2029 ( Figure 4C). Our results revealed that the SUA level was a valuable indicator in predicting the prognosis of IgAN patients, especially in female patients, which is consistent with the research of Oh et al (Oh et al 2020).…”
Section: The Value Of the Sua Level In Predicting Renal Prognosissupporting
confidence: 93%
“…4C). Our results revealed that the SUA level was a valuable indicator in predicting the prognosis of IgAN patients, especially in female patients, which is consistent with the research of Oh et al (2020).…”
Section: The Value Of the Sua Level In Predicting Renal Prognosissupporting
confidence: 90%
“…Comparable findings were also reported in a study conducted in Japan showing increased serum uric acid among the smoking population 14 . Although the reason for the positive association between smoking exposure and hyperuricemia only in women is unclear, prominent renal function declining in women with IgA nephritis might, at least partly, be related to this finding 21 . In addition, metabolic impairment due to smoking exposure could play a significant role in the risk for hyperuricemia, which is different between women and men 22 .…”
Section: Discussionmentioning
confidence: 96%